The Differential Effects of Auditory and Visual Stimuli on Learning, Retention and Reactivation of a Perceptual-Motor Temporal Sequence in Children With Developmental Coordination Disorder - Blais, Mélody; Jucla, Mélanie; Maziero, Stéphanie; Albaret, Jean-Michel; Chaix, Yves; Tallet, Jessica (Frontiers in Human Neuroscience, 2021)
The present study investigates procedural learning, retention and reactivation of temporal sensorimotor sequences in children with and without DCD. Twenty typically-developing (TD) children and twelve children with DCD participated in this study. Children were required to tap on a keyboard synchronizing with auditory or visual stimuli presented as an isochronous temporal sequence, and to practice non-isochronous temporal sequences in order to memorize them. Immediate and delayed retention of the audio-motor and visuo-motor non-isochronous sequences were tested by removing auditory or visual stimuli immediately after practice and after a delay of 2 hours. A reactivation test consisted in reintroducing the auditory and visual stimuli after the delayed recall. Data were computed with circular analyses to obtain asynchrony, stability of synchronization and errors (i.e., the number of supplementary taps). Firstly, a global deficit in synchronization with both auditory and visual isochronous stimuli was observed in DCD children compared to TD children. During practice, better improvements (decrease of asynchrony and increase of stability) were found for the audio-motor non-isochronous sequence compared to the visuo-motor non-isochronous sequence in both TD children and DCD groups. However, a drastic increase of errors occurred in children with DCD during immediate retention, as soon as the auditory stimuli were removed. The reintroduction of auditory stimuli decreased the errors of the audio-motor sequence in children with DCD. Such changes were not seen for the visuo-motor non-isochronous sequence which was equally learnt, retained and reactivated in DCD and TD children. All these results suggest that TD children benefit from both auditory and visual stimuli to memorize the sequence whereas children with DCD seem to present a deficit in integration of the audio-motor sequence in memory. The immediate effect of reactivation suggests a specific dependency for the auditory information in DCD. Contrary to the audio-motor sequence, the visuo-motor sequence is both learnt and retained in DCD. This suggests that visual stimuli could be the best information to memorize a temporal sequence in DCD. All these results are discussed in terms of a specific audio-motor coupling deficit in DCD.